Awareness and Knowledge about Contraceptive Practices and Emergency Contraception in Paramedical Staff Working in a Tertiary Care Hospital of Karachi, Pakistan (Medical Forum Monthly, 2024)
Objectives: The study was revolving on means to explore comprehensions regarding different contraceptive methods including emergency contraception among primary health care providers (HCP) {Registered Staff Nurse (RN), Lady Health Visitor (LHV) and Midwives (MW)} in tertiary care hospital of Karachi.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of from Physiology / Community Health Sciences, Shaheed Mohtarma Benazir Bhutto Medical College, Lyari, Karachi from Dec. 2015 to June 2016Materials and Methods: Female employees in the reproductive age group either with marital or non marital status were interviewed. A survey performa containing both open and close type questions was utilized.Results: 258 females assented for the participation. All the female participants were educated and bulk (97.2%) had a metropolitan background. Out of 190 married females, 154 (81.1%) used various birth control methods; among them (73.3%) were on and off users. fifty participants undergone termination of pregnancy, out of which 46 had natural and 34 had persuaded intentional termination of pregnancy. Amidst the accessible contraceptive techniques, condom was the popular method in 89 (57.8%) after which Copper T in 38 women (24.7%). Regarding hormonal contraceptives the use was very low, which is only 2.6%. Newspapers and television were the widespread source of public awareness in 149 subjects (57.7%). Only 29 females (11.2%) were sentient and three females utilized emergency contraception once in their life.Conclusion: A large number of educated working HCP has awareness and knowledge about use of contraception; conversely, the knowledge about use of emergency contraception was very low.